ANALYSIS OF THE ARCHITECTURE OF THE ELECTRONIC HEALTH CARE SYSTEM AND THE MAIN PROBLEMS OF INTEROPERABILITY - FILIPOVA, Nataliia; MYKHAILOVSKA, Olena; KOLOTOV, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive analysis of the architecture of Ukraine’s Electronic Health System (EHS) with particular emphasis on the challenges of interoperability. The study highlights that EHS is a key element of the digitalization of healthcare services, designed to ensure automated exchange of medical information among patients, healthcare providers, institutions, and state bodies. The research identifies core interoperability barriers, such as insufficient integration of medical information systems, discrepancies in technological solutions, and lack of standardized data protocols. Special attention is given to the issues of semantic, syntactic, technical, functional, and legal interoperability, demonstrating their significance for seamless medical data exchange.The analysis also examines the functionality of the EHS, including electronic declarations, e-prescriptions, medical certificates, COVID-19 vaccination records, and integration with government registries. By combining a centralized database operated by the state with decentralized medical information systems developed by private vendors, the EHS functions on a public-private partnership model. This approach ensures flexibility, security, and scalability of healthcare digitalization. The paper further outlines the system’s advantages for patients, healthcare institutions, and the state, such as improving treatment quality, optimizing resources, enhancing transparency, and strengthening patient data protection.The results show that while significant progress has been made in establishing interoperability—particularly through international standards such as ICD-10, ICPC-2, and HL7 FHIR—there remain challenges at the functional and legal levels due to entrenched organizational practices and regulatory gaps. To address these, the authors propose stronger standardization, modernization of infrastructure, and active collaboration among government, medical institutions, and business stakeholders. Achieving full interoperability is essential not only for improving healthcare efficiency and patient safety but also for aligning Ukraine’s digital health sector with international standards and supporting sustainable reforms.
Keywords: electronic health care system; interoperability; system architecture; EHS functionality; digitalization; management